2015
DOI: 10.1007/s13197-015-1739-x
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of low-calorie orange nectar containing stevioside

Abstract: The study was carried out to produce and characterize a low-calorie orange nectar using response surface methodology (RSM). To optimize the formulation, three different levels of independent variables; sugar, stevioside and pectin and two responses of Brix and viscosity were selected. In the optimum formulation, sugar content reduced to 70 % (compared to control sample) using stevioside and pectin with maximum levels of 0.06 and 0.03 %, respectively. Physicochemical properties of optimal and control samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(31 reference statements)
4
1
1
Order By: Relevance
“…They also reported that in case of blueberry juice, the viscosity increased from 2.9 to 184 mPas. However, the results for viscosity in this study on Indian blackberry nectar contradict the findings of Hosseini et. al (2015) who observed a 10 per cent reduction in viscosity during storage of stevioside containing orange nectar of low calorific value.…”
Section: Viscositycontrasting
confidence: 99%
See 2 more Smart Citations
“…They also reported that in case of blueberry juice, the viscosity increased from 2.9 to 184 mPas. However, the results for viscosity in this study on Indian blackberry nectar contradict the findings of Hosseini et. al (2015) who observed a 10 per cent reduction in viscosity during storage of stevioside containing orange nectar of low calorific value.…”
Section: Viscositycontrasting
confidence: 99%
“…Lower levels of acidity in refrigerated nectar compared to the one held at ambient temperature could happen because of lower rates of chemical reactions at low temperature. This finding is in conformity with the one reported by Hosseini et. al (2015) in orange nectar added with stevioside to make it low in calorific value.…”
Section: Changes In Physico-chemical Properties 311 Titratable Aciditysupporting
confidence: 94%
See 1 more Smart Citation
“…As described in Figure 2, minor increase in TTA was observed during the storage period, the values were ranged from (0.57–0.65) g/100 ml to (0.80–0.90) g/100 ml at 4°C and around (0.6–0.67) g/100 ml to (0.85–0.91) g/100 ml at 25°C. This data were in accordance with Barakat et al (2017), Hosseini et al (2015) who have reported the increment of TTA to the partial degradation of pectin. This increment can be also harmonized with either the antimicrobial potential of Stevia and orange juice composition according to Pina‐Pérez et al (2018) and Haraoui et al (2019).…”
Section: Resultssupporting
confidence: 93%
“…Hence, the addition of higher quantities of steviol glycoside (>25mg/100mL) can be recommended for retaining optimum sweetness in RTS beverages for six months storage. Other studies indicated the higher decrease in stevioside content (18%) in a low-calorie orange nectar prepared with reduced sugar content and high stevioside content (60 mg/100 mL) during storage at 25 °C for 2 months [28]. Some studies revealed that degradation of Rebaudioside A into six secondary compounds in carbonated beverages at pH 2.8-4.2 at various temperatures (5-40 °C) stored for six months [29].…”
Section: Changes In Physicochemical Parametersmentioning
confidence: 99%